The Activity of Students in Problem-Based Learning and Project-Based Learning Models to Improve Social Studies Learning Outcomes in Elementary Schools - Yayan Alpian; Sri Wulan Anggraeni; Nita Rohayati; Warsih Warsih (Universitas Pendidikan Ganesha, 2025)
Many students face challenges in engaging with social studies due to the traditional teaching methods that emphasize memorization rather than active learning. This study aims to explore the application of project-based learning and problem-based learning models in improving social studies learning outcomes in elementary schools, as well as to analyze the impact of student activity levels on their learning outcomes. The study focuses on addressing the issue of low student engagement and its effect on learning performance. The research uses a quantitative approach with a 2x2 factorial experimental design, involving two experimental groups: students learning with the project-based learning model and students learning with the problem-based learning model. Data were collected through essay-type learning outcome tests and questionnaires to measure student activity levels.The results show that the project-based learning model has a positive impact on students' learning outcomes, with an average score higher than that of the problem-based learning model. Additionally, student activity level also affects learning outcomes, with more active students showing better results. Two-way ANOVA testing revealed significant effects of the learning model, student activity, and their interaction on students' social studies learning outcomes. Based on these findings, it can be concluded that the project-based learning model is effective in improving student activity and learning outcomes.